Internet Use among First-Year University Students: Computer versus Mobile Phone Activities across Home, School and Community Contexts - Johnson, Genevieve (Association for the Advancement of Computing in Education, 2012)
Forty-eight first-year university students responded to an online survey regarding their use of internet applications on computers and mobile phones at home, school and in the community. Results suggest that university students are not unanimously connected; five of 48 students who completed the survey indicated that they did not use the internet at home and six reported that they did not use the internet at university. Across all environments, accessing the internet via computer or mobile phone was most commonly reported for purposes of communication. Students used a limited range of specific internet applications. Approximately one-third of students used their mobile phones for school work. When considering instructional applications of internet technology, mobile phones appear useful to some learners. Student access to learning opportunities and instructional resources may be the most beneficial aspect of the internet and mobile phones.